POLA ASUH ORANG TUA DALAM PEMBELAJARAN DARING DI MASAPANDEMI COVID-19 - Mariska Nadya Putri; Irfai Fathurohman; Deka Setiawan (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to determine the parents' parenting style during online learning during the pandemic in Plangitan Pati village. The results of this study indicated that the parents applied a democratic parenting style to educate, give attention, provide family affection, and encourage learning to their children. They provided positive things for children during online learning so that children did not feel bored. The children did not feel that they had many difficult tasks. Parents always provided a good way for children not to get bored easily in learning. Online learning made children feel like they had a daily task and many responsibilities for their tasks. As a result, children felt bored more than enthusiastic about learning. Based on this study results, only one child was delighted and faced no difficulty in online learning because it used WhatsApp, classroom, and zoom applications